2007
DOI: 10.1186/1752-0509-1-44
|View full text |Cite
|
Sign up to set email alerts
|

Consistency analysis of metabolic correlation networks

Abstract: Background: Metabolic correlation networks are derived from the covariance of metabolites in replicates of metabolomics experiments. They constitute an interesting intermediate between topology (i.e. the system's architecture defined by the set of reactions between metabolites) and dynamics (i.e. the metabolic concentrations observed as fluctuations around steady-state values in the metabolic network).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 40 publications
2
45
0
Order By: Relevance
“…However, initial metabolome experiments (Roessner et al, 2001) as well as simulation studies (Steuer et al, 2003;Müller-Linow et al, 2007) have shown that correlations do not necessarily reflect the pathway architecture. More specifically, profiling studies of mainly primary metabolites (Roessner et al, 2001) have shown that most metabolite pairs have low correlation coefficients and only a few metabolite pairs are highly correlated.…”
Section: Cspp Network Do Not Show a Small World Behaviormentioning
confidence: 99%
“…However, initial metabolome experiments (Roessner et al, 2001) as well as simulation studies (Steuer et al, 2003;Müller-Linow et al, 2007) have shown that correlations do not necessarily reflect the pathway architecture. More specifically, profiling studies of mainly primary metabolites (Roessner et al, 2001) have shown that most metabolite pairs have low correlation coefficients and only a few metabolite pairs are highly correlated.…”
Section: Cspp Network Do Not Show a Small World Behaviormentioning
confidence: 99%
“…For instance, in a recent study by Muller-Linow et al (2007), GC-MS analysis could only map 39 of the measured metabolites on the metabolic pathways. Another important issue concerning the coverage of metabolic pathways is the potential bias introduced by the extraction procedure and the equipment set-up.…”
Section: Coverage Of Metabolic Pathways By Ms Datamentioning
confidence: 99%
“…In systems biology, the comparison of metabolomics data with metabolic networks belongs to the same class of statistical problems (see, for example, [11,12]). A related question is network inference, i.e., how to estimate interaction networks from dynamical data.…”
Section: Introductionmentioning
confidence: 99%